Biological characterization of a novel mammalian antimicrobial peptide - Gennaro, Renato; Scocchi, Marco; Merluzzi, Laura; Zanetti, Margherita (Biochimica et biophysica acta, 1998)
A putative antimicrobial peptide of 34 residues was recently deduced from a bovine cathelicidin gene sequence and named BMAP-34. A peptide based on the deduced sequence was chemically synthesized and used to study the localization, structure and biological activities of BMAP-34. A Western blot analysis using antibodies raised to the synthetic peptide showed that BMAP-34 is stored as proform in the cytoplasmic granules of bovine neutrophils. CD spectroscopy indicates that the peptide assumes an amphipathic α-helical conformation, as also predicted by secondary structure analysis. The peptide exerts a broad spectrum antimicrobial activity against both Gram-negative and Gram-positive organisms, and is not active against eukaryotic cells. When tested on Escherichia coli ML-35, the kinetics of bacterial killing and of inner membrane permeabilization are slower than those observed for other α-helical peptides derived from cathelicidins.